Investigating the nuclear structure of 116,118Te - Topalis, Konstantinos; Violanti, Anna; Efstathiou, Margarita; Vasilieiou, Polytimos; Koseoglou, Pavlos; Mertzimekis, Theodoros; N.Mărginean; C. Mihai; R. Lică; C. Costache; A. Turturica; R.E. Mihai; et al. (HNPS Advances in Nuclear Physics, 2026)
The 116,118Te isotopes, similar to the Cd mid-shell isotopes which are their mirror partners across the 𝑍 =50 shell, show vibrational features on their ground-band states. However, recent density functional theory calculations and proxy-SU(3) studies also predict shape coexistence in these nuclei. More experimental data are needed in order to verify this. An experiment was conducted at the 9MV Tandem Accelerator at IFIN-HH in Magurele, Romania, in order to populate excited states in 116,118Te by the fusion evaporation reaction mechanism. An 11B beam at beam energy of 35 MeV was impinged on a 107,109Ag target. The subsequent gamma decay was detected using the RoSPHERE array, equipped with 15 HPGe and 10 LaBr3(Ce) detectors. The experiment provided data for spectroscopic analysis and highlighted the need for further refinement in experimental techniques, potentially incorporating the plunger technique to measure the ground-state band lifetimes in the future. In this contribution the gamma-spectroscopy analysis on 116,118Te will be presented. Consecutive work will focus on fast-timing measurements to determine the lifetimes of excited states.